2022
DOI: 10.1186/s42523-021-00158-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of the threatened takahē: biogeographic patterns and conservation implications

Abstract: Background The Aotearoa New Zealand takahē (Porphyrio hochstetteri), once thought to be extinct, is a nationally threatened flightless rail under intensive conservation management. While there has been previous research into disease-related microbes in takahē, little is known about the microbes present in the gastrointestinal tract. Given the importance of gut-associated microbes to herbivore nutrition and immunity, knowledge of these communities is likely to be of considerable conservation val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…There is mounting evidence that the microbiota of threatened species can be altered by factors including captivity [39][40][41][42], habitat fragmentation [43][44][45], climate change [46,47] and medical treatment [48,49], though how such changes may impact animal health remains uncertain [50]. While kākāpō reside on secluded offshore islands with limited human contact, they are, nonetheless, an intensively managed species, particularly during breeding seasons.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that the microbiota of threatened species can be altered by factors including captivity [39][40][41][42], habitat fragmentation [43][44][45], climate change [46,47] and medical treatment [48,49], though how such changes may impact animal health remains uncertain [50]. While kākāpō reside on secluded offshore islands with limited human contact, they are, nonetheless, an intensively managed species, particularly during breeding seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Among New Zealand birds, human-related alterations in microbial diversity have been documented for takahē (Porphyrio hochstetteri) and brown kiwi (Apteryx mantelli; Fig. 3) (San Juan et al 2021;West et al 2022b). In each case, 16S rRNA gene sequencing revealed that Lactobacillus bacteria were more prevalent in individual birds which were subjected to more intensive management (takahē) or captivity (brown kiwi).…”
Section: Birdsmentioning
confidence: 99%
“…Lactobacillus aviarius was ubiquitously detected in 57 takahē from across New Zealand, with its relative abundance reflecting the location from which the sample was obtained (West et al 2022b). Notably, the highest Lactobacillus abundances were at Burwood Takahē Centre, which provides the most intensive management.…”
Section: Birdsmentioning
confidence: 99%
“…The microbiota is intrinsic to animal health, fitness and development [Cho and Blaser 2012], with essential roles in digestion, homeostasis, immune system regulation, reproduction and neurological processes [Spor et al 2011; Gilbert et al 2018]. The potential influence of the gut microbiota on the health and fitness of threatened wildlife is pertinent to conservation management programmes, especially when it comes to captive or highly managed populations [Trevelline et al 2019; San Juan et al 2021; West et al 2019, 2022a, 2022b]. For example, fertility in both the critically endangered eastern black rhinoceros and threatened southern white rhinoceros was directly related to microbiota-mediated hormone production and metabolism [Antwis et al 2019; Williams et al 2019], enabling the identification of potential biomarkers of reproductive health to aid species conservation.…”
Section: Introductionmentioning
confidence: 99%
“…While the microbiota can be shaped by environmental factors such as diet, medication, habitat or social networks [David et al 2014; Rodrigues Hoffmann, 2017; Rothschild et al, 2018; San Juan et al 2021; West et al 2022a, 2022b], our understanding of the entirety of factors that shape the microbiota remains incomplete. Microbiota composition can, for example, be significantly associated with phylogeny [Waite and Taylor 2014; Rojas et al 2021], and can override substantial divergence in a species’ ecology (e.g., the gut microbiota of the herbivorous giant panda is similar to those of its carnivorous sister species [Xue et al 2015]).…”
Section: Introductionmentioning
confidence: 99%